FACTORS RELATED TO BEHAVIOR THE COMMUNITY IN DISPOSING OF GARBAGE IN THE VILLAGE OF BANGUNTAPAN - nor wijayanti (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
According to the American Public Health Association, the junk is defined as something that is not used, unused, unwanted or something disposed of, derived from human activities and does not happen by itself. Based on data from the Department of Environment Bantul Regency Year Of 2018 Producing the biggest waste there is in the District of Banguntapan by 264,49 m3/day while the lowest was 77,64 m3/day are in the District of Kretek. The results of the interviews in the community, it was found that as much as 45% of citizens have yet to separate or distinguish organic and inorganic waste. The purpose of this study was to determine the factors associated with the behavior of the community in disposing of garbage the Village of Banguntapan. This research uses descriptive quantitative with cross sectional approach. The sampling technique used is accidental sampling with a total sample of 76 respondents. The analysis used is the analysis of univariate and bivariate with Chi Square statistical test. The results of this research is on the analysis of the chi square showed no relationship between the factors with the behavior of the community in disposing of garbage as follows education with behavior sig. 0,002 (p<0,05), the income with the behavior of the sig. 0,037 (p < 0.05), availability of infrastructure gis. 0.000 (p<0.05). The conclusion obtained that there is significant relationship between education, income, availability of infrastructure to the behavior of the community in disposing of garbage in the Village of Banguntapan.